Abnormally primed CD8 T cells: The Achilles’ heel of CHB - Chen, Xiaoqing; Liu, Xue; Jiang, Yichao; Xia, Ningshao; Liu, Chao; Luo, Wenxin (Frontiers in Immunology, 2023)
Chronic hepatitis B virus (HBV) infection continues to be a significant public health challenge, and more than 250 million people around world are infected with HBV. The clearance of HBV with virus-specific CD8 T cells is critical for a functional cure. However, naïve HBV-specific CD8 T cells are heavily hindered during the priming process, and this phenomenon is closely related to abnormal cell and signal interactions in the complex immune microenvironment. Here, we briefly summarize the recent progress in understanding the abnormal priming of HBV-specific CD8 T cells and some corresponding immunotherapies to facilitate their functional recovery, which provides a novel perspective for the design and development of immunotherapy for chronic HBV infection (CHB). Finally, we also highlight the balance between viral clearance and pathological liver injury induced by CD8 T-cell activation that should be carefully considered during drug development.